Ethylene-induced Phenylalanine Ammonia-Lyase Activity in Carrot Roots - Chalutz, Edo (1973)
Ethylene enhanced the activity of phenylalanine ammonialyase in carrot (Daucus carota L., var. “Nauty”) root tissue. Slight increase in enzyme activity was exhibited by root discs incubated in ethylene-free air. It was probably due to the ethylene formed within the sliced tissue. Addition of ethylene to the air stream increased phenylalanine ammonia-lyase activity and the total protein content of the discs until maximum activity was reached after 36 to 48 hours of incubation. The continuous presence of ethylene was required to maintain high level of activity. Ethylene, at a concentration of 10 microliter per liter induced higher activity than at lower or higher concentrations. CO(2) partially inhibited the ethylene-induced activity. Cycloheximide or actinomycin D effectively inhibited the ethylene-induced activity in discs that had not previously been exposed to ethylene. The results appear to support the hypothesis that the mode of action of ethylene may involve both de novo synthesis of the enzyme protein and protection or regulation of activity of the induced enzyme.